Evidential Reasoning in Archaeology - Chapman, Robert (Debates in Archaeology Ser, 2016)
FC -- Half title -- Debates in Archaeology -- Title -- Copyright -- Contents -- List of Illustrations -- Acknowledgements -- Introduction: The Paradox of Material Evidence -- 1 Archaeological Evidence in Question: Working between the Horns of a Dilemma -- 2 Archaeological Fieldwork: Scaffolding in Practice -- 3 Working with Old Evidence -- 4 External Resources: Archaeology as a Trading Zone -- Conclusions: Reflexivity Made Concrete -- Bibliography -- Index.